PENGARUH PROMOSI DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN DI TOKOPEDIA - Eva Choirunisa; Rifki Hanif (Value : Jurnal Manajemen dan Akuntansi, 2023)
Technological developments lead to increasingly fierce competition in e-commerce. Tokopedia's marketing strategy in surviving in a competitive climate is promotion and brand ambassadors. This study aims to analyze the influence of promotions and brand ambassadors on purchasing decisions at Tokopedia by students of the Asia Institute of Malang. This study uses a quantitative method with a survey approach as a research design. The population of this study were 143 management students at the Asia Institute of Malang. The sample was determined using a purposive sampling technique with the criteria of an active Tokopedia user so that the total sample is 104 people. Research data was collected through a questionnaire. Data analysis was performed using multiple linear regression techniques, t test and F test to test the significance of the influence of promotions and brand ambassadors on purchasing decisions. The results of the study show that promotion has a positive and significant influence on purchasing decisions at Tokopedia. Likewise, brand ambassadors also have a positive and significant influence on purchasing decisions. In addition, the results of the F test show that there is a significant simultaneous influence between promotions and brand ambassadors on product purchasing decisions at Tokopedia. Keywords: Brand Ambassador, Promotion, Purchase decision